The Consultation Machine: Experiments in AI Futures, Literacies and Public Participation - McKelvey, Fenwick; Jones, Maurice; Marinov, Robert; Frizzera, Luciano; Wester, Meaghan (Imaginations, 2026)
The Consultation Machine was our third attempt to create a workshop for publics to engage and debate AI futures. Our efforts devolved from sincere attempts to use strategic foresight to shape AI policy, towards AI-assisted future-making, and finally to the Consultation Machine. We document these three different prototypes to explain the evolution of their design, shaped by participatory methods, and to critically reflect on the results. Our efforts add to a growing literature investigating how AI changes democratic policy making in technoscientific capitalist systems, wherein democracy may yet become just another “problem” to be streamlined and automated by algorithmic “solutions.”